What’s the use of educational research? Six stories reflecting on research use with communities - Rudolph, Sophie; Mayes, Eve; Molla, Tebeje; Chiew, Sophie; Abhayawickrama, Natasha; Maiava, Netta; Villafana, Danielle; Welch, Rosie; Liu, Ben; Couper, Rachel; Duhn, Iris; Fricker, Al; et al. (Springer Science and Business Media LLC, 2025)
The question of how education research can be ‘useful’ is an enduring and challenging one. In recent years, this question has been approached by universities through a widespread ‘impact’ agenda. In this article, we explore the tensions between usefulness and impact and present six stories that reflect on research use with communities. These stories engage issues of the risk of usefulness, the time that is needed to work collaboratively for research usefulness, whether theories developed in universities can be useful to communities for understanding the problems they face, who has the power to steer research to serve their purposes, and how community collective action can enhance the usefulness of research. The article concludes with a section that reflects on the importance of continuing to engage with the debates about research use in often highly commercially oriented university environments. This article brings together diverse voices that wrestle with the politics of research use beyond the neat, linear narratives of change that impact agendas tend to portray. These illustrations of the ethical dilemmas encountered through navigating research use with communities contribute to an ongoing conversation about refusing capitalist and colonialist logics of research extraction while working within institutions often driven by such logics.